Development of Stability Indicating Media for In-Vitro Dissolution Testing of Didanosine in Pharmaceutical Dosage Forms - Nagiat T. Hwisa1 and Babu Rao Chandu1,3, Prakash Katakam1,2*, A. Shanta Kumari2 (Recent Research in Science and Technology, 2011)
The present investigation is aimed at developing the stability indicating dissolution media for the determination of didanosine (DDI, a HIV-1 Reverse Transcriptase inhibitor) in pharmaceutical dosage forms for the first time. The stability of didanosine was tested in various dissolution media, ie., 0.1M HCl, pH 1.2 KCl-HCl buffer and pH 5.8, 6.2, 6.6, 7.0, 7.4 and 7.8 phosphate buffers separately. The stability was tested at room temperature and 37oC for 48 hrs. The samples were scanned for stability and the optimized samples were selected for further study. Stability studies of DDI in various media at RT and 37oC indicated that the drug is stable in pH 1.2 KCl-HCl buffer, pH 6.2 and pH 7.0 phosphate buffers in the UV region for a period of 48 hr. The λmax were found to be 248.4, 249.3 and 254.4 nm for pH 1.2 KCl-HCl buffer, pH 6.2 and pH 7.0 phosphate buffers respectively with observed low coefficient of variation of <2.81%. Standard graphs were constructed in the above three media and linearity of the graphs were found to be in the range of 0.2-60, 0.2-40 and 0.5 – 40 µg/ml in pH 1.2 KCl-HCl buffer, pH 6.2 and pH 7.0 phosphate buffers respectively. The methods were validated and found to be precise, accurate and robust. These methods can be used for routine assay of DID in various dosage forms. In-vitro dissolution testing indicated that the drugs are stable and drug release is uniform for all dosage forms. It is concluded that the three optimized media could be used as dissolution media as simulated gastric fluid (pH 1.2 KCl-HCl buffer) and simulated intestinal fluids (pH 6.2 and pH 7.0 phosphate buffers) to study the dissolution profiles of DDI. Further these methods can be extended to bioequivalence studies of newly developed formulations of DID in the selected liquid media for both conventional and extended release dosage forms.